Teaching English Trough Collaborative Work - Mirzoyan, Irina
В статье рассматривается преподавание английского языка по технологии совместной работы. Сотрудничество налаживается для того, чтобы ученик приобрел знания и способы деятельности, опыт общения и социальной активности. Задача учителя в процессе сотрудничества создать реальную ситуацию общения, которая требует от участников проявления познавательной активности внутри коллектива. Обучение в сотрудничестве обеспечивает не только успешное освоение учебного материала, но и способствует интеллектуальному развитию учащихся, их активности и самостоятельности в достижении поставленной цели. В результате процесс обучения становится более интерестным, целенаправленным и эффективным. Collaboration is organized so as to make the pupil acquire knowledge, means of activities, communication experience and social activity. The aim of a teacher is to create a real situation of communication which will demand from participants to show their cognitive activity among group-members during the collaborative process of teaching. Collaborative teaching provides not only successful understanding of the academic material, but it also promotes intellectual development of pupils, their activity and achievement of their aims independently. As a result the process of teaching becomes more interesting, purposeful and effective.
Keywords: English teaching methods